Avaliação do efeito do zinco nas variáveis térmicas, microestrutura e propriedades mecânicas da liga Sn-34%Bi solidificada direcionalmente - Carvalho, Cássia Carla de (2022)
Due to environmental and human health issues related to the use of lead-containing alloys for applications in soldered joints of electronic microcomponents, it is necessary to study new soldering alloys with less toxicity and similar properties to the Sn-Pb system alloys. In this sense, Sn-Bi alloys have emerged as promising alternatives, since they have high mechanical and creep resistance and low cost. However, they exhibit disadvantages such as low ductility and segregation. One way to improve such characteristics is to add ternary alloying elements such as zinc (Zn), which can refine the microstructure, increase mechanical properties and inhibit Bi segregation in Sn-Bi alloys. Thus, the present proposal aims to evaluate the effect of adding Zn (0.5% and 9% by weight) on the microstructure, thermal parameters (cooling rateṪL and solidification speed-VL), segregation and mechanical properties of Sn-34%Bi-xZn alloys solidified directly under transient heat flow conditions. For this, the samples have been identified by Optical Microscopy (OM), Scanning Electron Microscopy (SEM), X-Ray Fluorescence (XRF) and X-Ray Diffraction (XRD), in addition to mechanical tests such as Vickers microhardness and traction. Thermodynamic simulations via Thermo-calc have been carried out to obtain information such as transformation temperatures, solidification paths, types of phases and their fractions. The microstructure for Sn-Bi-Zn alloys is completely dendritic, composed of an Sn-rich matrix (β-Sn) with Bi precipitates (with spherical, ellipsoidal and plate-type morphologies) in its interior and surrounded by a eutectic mixture of the β-Sn and α-Bi phases predominantly in the coarse scale, with the Sn-34wt.%Bi-9wt.%Zn alloy exhibiting Zn primary needles. The additions of Zn in the Sn-Bi binary alloy increased the VL values, while the 9wt.%Zn content increased the ṪL values. In addition, the Zn caused a coarsening of the dendritic arrangement, except for the tertiary dendritic spacing for the Sn34wt.%Bi-0.5wt.%Zn alloy. The Zn content remained constant throughout the Sn-34wt.Bi0.5wt.%Zn casting, while for the alloy with 9wt.%Zn addition, it presented a normal type macrosegregation profile. Both additions caused inverse-type macrosegregation profiles for bismuth, differing from the Sn-Bi binary alloy. The additions of Zn promoted an increase in Vickers microhardness and yield strength (σy) and ultimate tensile strength (σu), mainly for more refined microstructures, however, not reflecting on specific elongation values (δ). The Sn-34wt.%Bi-0.5wt.%Zn and Sn-34wt.%Bi-9wt.%Zn alloys exhibit ductile and brittle, and brittle (cleavage) fracture modes, respectively.